A146 DIETARY INTAKE OF PATIENTS WITH CROHN'S DISEASE IN REMISSION: A CROSS-SECTIONAL STUDY. (1st March 2018) - Taylor, L; Almutairdi, A; Reimer, R; Madsen, K; Ghosh, S; Panaccione, R; Shommu, N; Fedorak, R; Raman, M
Abstract: Background: Many patients with inflammatory bowel disease (IBD), particularly Crohn's disease (CD) suffer from macro- and micronutrient deficiencies and do not meet current evidence-based guidelines for dietary intake. The intake patterns of these patients have not been well documented. Aims: To describe the (a) macro- and micronutrient intake and (b) dietary servings of red meat, poultry, fish, fruits, vegetables and probiotic containing foods in a cohort of patients with CD in remission from a single tertiary care center. Methods: Adult CD patients in endoscopic and clinical remission with ileal or ileocolonic disease were recruited prospectively at the University of Calgary. Patients completed a detailed 3-day food diary, which was reviewed with the patient by a registered dietitian (RD). Nutrient analysis was completed using ESHA, a nutrition analysis program. Research ethics board approval was obtained. Results: Fifty-nine patients meeting inclusion and exclusion criteria were consecutively recruited (27 males and 32 females). The mean intake of nutrients, servings of meat, fruit and vegetables, and probiotics were calculated for each gender and compared to dietary reference intakes (DRI) and Canada's Food Guidelines (CFG) for healthy populations. The mean total calories, carbohydrates, fat, and fiber intake did not meet DRI (68%, 58%, 85% and 50%) respectively. Protein mean intake was high with males and females consuming 168% and 150% of their DRI respectively. Apart from the micronutrients, vitamins D, E, K, calcium, magnesium, potassium, and folate, the mean intake of the remaining vitamins was close to the DRI for both genders. Vitamin D mean intake was the lowest among the vitamins, with patients consuming less than 20% of the DRI in both genders. Servings of fruits and vegetables per day was low, 50% of the recommended daily servings as per the CFG in our study population. Mean weekly red meat servings were six, (600grams/week). No study patients ingested probiotic-containing foods. Conclusions: Even among patients in clinical and endoscopic remission, patients with Crohn's disease have inadequate dietary intake and decreased dietary diversity. The impact on the natural history of disease is unknown. However, patient-centered dietary counseling would likely be beneficial in this patient population. Funding Agencies: Broad Foundation